(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Some power plants use sand filtering, ion exchange, and chemical decarbonization to create boiler water. Ion exchange in a mixed bed completes this procedure. On the basis of the water quality that is attained, the amount and quality of the water, and the necessary chemical dosages, the current boiler water treatment processes are assessed. The extensive usage of chemicals in present systems is a serious flaw. Reverse osmosis can take the role of the ion exchange process; however, pretreatment (decarbonization and filtering) must still be used. This investigation’s goal is to assess how well pretreated water performs in the boiler unit of a food processing facility in Borg El Arab, Alexandria, Egypt. Oxygen scavengers like sulfites, tannins, DEHA, and carbohydrazides, flocculants like poly-aluminum chloride and aluminum sulphate (liquid), and lime scale inhibitors like polyphosphates, hexametaphosphates, and polyphosphates are all the subject of current research. Salt or another flocculating agent was utilised. Results indicated that, when compared to other oxygen scavengers utilized in the study, alum coagulant, polyphosphate mineralizer, and carbohydrazide were more efficient than PAC